Rolling-out Lean in the Saskatchewan Health Care System: Politics Derailing Policy - Tom McIntosh (McMaster University Library Press, 2016)
Following on the work of Marchildon (2013) this paper examines the political challenges faced by the government of Saskatchewan in rolling out their Lean reforms to the entire provincial health system. The government's Lean reforms were meant as a vehicle to empower patients and workers in the redesign of service delivery and the creation of a patient-centred system. Lean focuses on continuous improvement, priority setting, employee engagement and the elimination of waste. The reforms appear to have been derailed to a significant degree insofar as key actors inside the system, the media and the public have challenged the goals of the reform, the Lean methodology and process, as well as the cost of the consultants employed to oversee the process. The government's implementation of the roll-out suffered both from the ability of key actors to withdraw their support and challenge the viability of the reforms in public as well as from a public relations perspective that put the government on the defensive about how people inside the system were being treated with the reforms. As the government moves forward it will have to adjust its implementation processes and strategy in order to overcome the now strong resistance within the health sector. Cet article fait suite à celui de Marchildon (2013) et étudie les obstacles politiques rencontrés par le gouvernement en Saskatchewan quand il a voulu étendre ses réformes « Lean » au système de santé dans son ensemble. Par ces réformes, le gouvernement voulait donner leur mot à dire aux patients et aux producteurs de soins dans la recomposition de la délivrance des soins et la création d'un système centré sur le patient. « Lean » vise l'amélioration permanente, l'établissement de priorités, l'engagement des employés et la chasse au gaspillage. Il semble que les réformes aient achoppées pour une bonne part parce que des acteurs clé à l'intérieur du système, les média et le public ont remis en cause leurs objectifs, la méthodologie et le processus de « Lean », ainsi que les coûts des consultants employés pour conduire le processus. La mise en place de la généralisation par le gouvernement a été malmenée à la fois par la capacité des acteurs clé de retirer leur soutien et de remettre en cause publiquement la faisabilité des réformes, mais aussi par une opération de relations publiques ayant contraint le gouvernement à défendre la façon dont les personnels étaient traités par les réformes. Quand le gouvernement voudra avancer sur ce dossier, il devra ajuster les processus de mise en place et sa stratégie afin de dépasser des réticences maintenant fortes au sein du secteur sanitaire.